2016
DOI: 10.18632/oncotarget.7756
|View full text |Cite
|
Sign up to set email alerts
|

Tumor deposits counted as positive lymph nodes in TNM staging for advanced colorectal cancer: a retrospective multicenter study

Abstract: We investigated the possibility of counting tumor deposits (TDs) as positive lymph nodes (pLNs) in the pN category and evaluated its prognostic value for colorectal cancer (CRC) patients. A new pN category (npN category) was calculated using the numbers of pLNs plus TDs. The npN category included 4 tiers: npN1a (1 tumor node), npN1b (2-3 tumor nodes), npN2a (4-6 tumor nodes), and npN2b (≥7 tumor nodes). We identified 4,121 locally advanced CRC patients, including 717 (11.02%) cases with TDs. Univariate and mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…However, TNM staging fails to evaluate survival outcomes accurately in many patients undergoing surgical resection [ 5 ]. Conflict outcomes even existed among patients with same stage category [ 6 , 7 ]. Besides that, although the version of TNM staging has been continuously updating in the past decade, the prognosis value does not increase significantly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, TNM staging fails to evaluate survival outcomes accurately in many patients undergoing surgical resection [ 5 ]. Conflict outcomes even existed among patients with same stage category [ 6 , 7 ]. Besides that, although the version of TNM staging has been continuously updating in the past decade, the prognosis value does not increase significantly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with CRC has gradually improved in recent decades, however, many issues remain to be resolved. Changes in the definition of TDs have caused considerable confusion among researchers and have had a significant impact on the choices of post-operative treatment and on precise prognosis ( 13 ). Gabriel et al depicted TDs as a result of vascular tumor dissemination in 1935, however, given that TDs were located in the pericolic or perirectal fattiness not continuous with the primary tumor and unassociated with nodes, it was difficult to distinguish between TDs and LNs ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of counting TDs as the number of positive lymph nodes (pLNs) in the CRC has recently been investigated, and the results indicated that counting TDs as pLNs improved the predictive ability for assessing prognosis and survival in patients with CRC (12,13). However, previous studies only included a limited number of Asian patients, with no validation cohorts from western countries.…”
Section: Introductionmentioning
confidence: 99%
“…Although the TNM staging system is widely used as the risk stratification of CRC patients, it is insufficient in the prediction of prognosis and estimation for some patients. 32 , 33 Conflict clinical outcomes may exist among some CRC patients with the same stage. 31 , 32 To date, there are no clinically utilized prognostic biomarkers in CRC patients.…”
Section: Discussionmentioning
confidence: 99%